Metacognition as a graduate attribute: Employability through the lens of self and career literacy - Bennett, Dawn (2017)
Context: Although engineering employability receives significant attention both nationally and internationally, there is little agreement about how employability should be defined or how it might be developed through an integrated approach. Definitions aside, student engineers need to prepare for careers that are increasingly unstable, mobile and self-directed. In the current climate, employability in engineering can no longer be defined as a job: it does not come with the graduation certificate or with accreditation and it requires constant work throughout the career lifecycle. Purpose: This study positioned employability development as the cognitive and social development of student engineers as capable and informed individuals, professionals and social citizens. The study located employability development within the existing curriculum and sought to engage students as partners in their developmental journeys by creating a better understanding of students’ thinking as student engineers. Approach: The study employed a new measure of self and career literacy to develop personalised engineering profiles with 255 first-year engineering students. Students self-assessed their employability development using an online tool. Using the same process, educators will draw on students’ self-assessments to rethink the design and delivery of initial engineering education, including composite forms of work-integrated-learning. Results: Early results indicate the value of a metacognitive approach to employability development. The measure revealed students’ perceptions of their development as engineers. The inclusion of ‘self’ alongside ‘career’ revealed new insights on ‘basic’ career literacy, with students emphasising the need for high-level communication skills and a desire for work that has meaning and impact. Conclusions: Employability development is a career-long concern in which higher education plays an intensive early role. Involving students in this process from the first year of studies has the potential for students to realise their individual roles as partners in the developmental process. The findings illustrate that the successful integration of engineering theory and practice requires students to become agentic partners in their personal development. For this to occur, educators need to understand students’ perceived weaknesses and strengths, and areas in which they might be over-confident. The study reaffirms that it is insufficient for students to know how to think; they need a critical awareness and understanding of their thinking and learning processes. It is imperative, then, that metacognition forms the basis of an integrated engineering education.